Evaluation of fat mass and its correlation with abnormal blood pressure in children and adolescents - Pirogowicz, Iwona; Ornat, Maciej; Pachołek, Krzysztof; Pawelak, Agnieszka; Domeredzka, Paulina; Jerczak, Bartosz; Gojny, Łukasz (Family Medicine & Primary Care Review, 2017)
Background. The problem of developmental obesity is growing in most countries of the world, reaching an epidemic. Excessive body weight in childhood results in a greater likelihood of obesity in adulthood, as well as causing endocrine, orthopedic, cardiological and psychogenic disorders. Overweight and obesity appear to be the most important causative factor. Objectives . The aim of the study was to estimate the usefulness of body composition analysis in predicting high blood pressure among children and adolescents and the correlation between the parameters of body mass and blood pressure (BP). Material and methods . Children from the age of 8 to 15 with recurrent respiratory tract diseases were selected during a rehabilitation and wellness stay in CRR KRUS in Szklarska Poreba. Body composition analysis was performed using the Tanita MC-780MA analyzer, and blood pressure was measured with a dial gauge. The study was conducted between 2015 and 2016, creating a database of 325 results sets. Results . Statistically significant correlations between systolic blood pressure, diastolic blood pressure, body weight and fat mass content were shown (p < 0.001). BMI and body fat content correlations were also statistically significant (p < 0.001). Conclusions . There is a problem of under-diagnosis of hypertension in the pediatric population. Obesity and overweight are connected with abnormal BP and hypertension. The total content of fat mass correlates with abnormal BP and hypertension.